Randomized controlled trial of the effects of high intensity and low-to-moderate intensity exercise on physical fitness and fatigue in cancer survivors: results of the Resistance and Endurance exercise After ChemoTherapy (REACT) study. Issue 1 (December 2015) - Kampshoff, Caroline; Chinapaw, Mai; Brug, Johannes; Twisk, Jos; Schep, Goof; Nijziel, Marten; van Mechelen, Willem; Buffart, Laurien
Abstract Background International evidence-based guidelines recommend physical exercise to form part of standard care for all cancer survivors. However, at present, the optimum exercise intensity is unclear. Therefore, we aimed to evaluate the effectiveness of a high intensity (HI) and low-to-moderate intensity (LMI) resistance and endurance exercise program compared with a wait list control (WLC) group on physical fitness and fatigue in a mixed group of cancer survivors who completed primary cancer treatment, including chemotherapy. Methods Overall, 277 cancer survivors were randomized to 12 weeks of HI exercise (n = 91), LMI exercise (n = 95), or WLC (n = 91). Both interventions were identical with respect to exercise type, duration and frequency, and only differed in intensity. Measurements were performed at baseline (4–6 weeks after primary treatment) and post-intervention. The primary outcomes were cardiorespiratory fitness (peakVO2 ), muscle strength (grip strength and 30-second chair-stand test), and self-reported fatigue (Multidimensional Fatigue Inventory; MFI). Secondary outcomes included health-related quality of life, physical activity, daily functioning, body composition, mood, and sleep disturbances. Multilevel linear regression analyses were performed to estimate intervention effects using an intention-to-treat principle. Results In the HI and LMI groups, 74 % and 70 % of the participants attended more than 80 % of the prescribed exercise sessions, respectively (P  = 0.53). HI (β = 2.2; 95 % CI, 1.2–3.1) and LMI (β = 1.3; 95 % CI, 0.3–2.3) exercise showed significantly larger improvements in peakVO2 compared to WLC. Improvements in peakVO2 were larger for HI than LMI exercise (β = 0.9; 95 % CI, −0.1 to 1.9), but the difference was not statistically significant (P  = 0.08). No intervention effects were found for grip strength and the 30-second chair-stand test. HI and LMI exercise significantly reduced general and physical fatigue and reduced activity (MFI subscales) compared to WLC, with no significant differences between both interventions. Finally, compared to WLC, we found benefits in global quality of life and anxiety after HI exercise, improved physical functioning after HI and LMI exercise, and less problems at work after LMI exercise. Conclusions Shortly after completion of cancer treatment, both HI and LMI exercise were safe and effective. There may be a dose–response relationship between exercise intensity and peakVO2, favoring HI exercise. HI and LMI exercise were equally effective in reducing general and physical fatigue. Trial registration This study was registered at the Netherlands Trial Register [NTR2153 ] on the 5th of January 2010.